Optimized hybrid nanospheres immobilizing Rhizomucor miehei lipase for chiral biotransformation. Issue 2 (February 2016) - Verri, F.; Diaz, U.; Macario, A.; Corma, A.; Giordano, G.
Graphical abstract: Highlights: Hybrid-nanosphere form has been applied to lipase immobilization. The use of surfactant to obtain mesoporous silica shell allowing reagent and product diffusion. Optimized hybrid-nanospheres are favorable biocatalysts for stereoselective reactions. The productivity of the prepared biocatalyst is 16-fold higher than that of free lipase. Optimized heterogeneous catalysts exhibit potential application in the pharmaceutical industry. Abstract: In this study, the immobilization of Rhizomucor miehei lipase into hybrid nanospheres containing a liposomal core was reported. Organic internal liposomal enzyme phase was protected by inorganic silica matrix, obtained with and without surfactant, that stabilizes the internal organic phase and isolates and protects the bioactive molecules. The optimized heterogeneous catalyst thus prepared was used for enantioselective esterification of (R, S)-ibuprofen. The influence of several catalytic parameters on the activity of hybrid nanospheres (type of solvent, nature of the alcohol, reaction temperature, etc., ) was investigated. The heterogeneous biocatalysts best performed at 37 °C, using isooctane as solvent and 1-propanol as alcohol (with ester yield ranging between 78 and 93%). High activity and stability (up to nine reaction cycles) of enzyme-immobilized hybrid nanospheres, with respect to the free form, were observed. R. miehei lipase, both in its free and immobilized forms, reacts only with the S(+) enantiomer of (R, S)-ibuprofen, in all the tested reaction conditions.